Discovery of biomarker candidates associated with the risk of short-term and mid/long-term relapse after infliximab withdrawal in Crohn's patients: a proteomics-based study. Issue 8 (26th October 2020) - Pierre, Nicolas; Baiwir, Dominique; Huynh-Thu, Vân Anh; Mazzucchelli, Gabriel; Smargiasso, Nicolas; De Pauw, Edwin; Bouhnik, Yoram; Laharie, David; Colombel, Jean-Frédéric; Meuwis, Marie-Alice; Louis, Edouard
Abstract : Objective: A subset of Crohn's disease (CD) patients experiences mid/long-term remission after infliximab withdrawal. Biomarkers are needed to identify those patients. Design: New biomarkers of relapse were searched in the baseline serum of CD patients stopping infliximab when they were under combined therapy (antimetabolite and infliximab) and stable clinical remission (diSconTinuation in CrOhn's disease patients in stable Remission on combined therapy with Immunosuppressors cohort, n=102). From shotgun proteomics experiment (discovery step), biomarker candidates were identified and further targeted by selected reaction monitoring (verification step). The dataset was stratified to search for markers of short-term (<6 months) or mid/long-term relapse (>6 months). The risk of relapse and the predicting capacity associated with biomarker candidates were evaluated using univariate Cox model and log-rank statistic, respectively. To test their complementary predicting capacity, biomarker candidates were systematically combined in pairs. Results: Distinct biomarker candidates were associated with the risk (HR) of short-term (15 proteins, 2.9<HR<16.1, p<0.05) and mid/long-term (17 proteins, 2.1<HR<4.7, p<0.05) relapse, they reflect different pathophysiological processes. In stratified and non-stratified datasets, novel marker combinations exhibited a high predicting capacity as shown by their higher Z-scores (false discovery rate <0.001) than C reactive protein and faecal calprotectin (current references in predicting relapse). Conclusion: We identified for the first time circulating biomarker candidates associated with the risk of mid/long-term relapse in CD patients stopping infliximab. We also highlight a sequence of pathophysiological processes leading to relapse, this could help to better understand the disease progression. Our findings may pave the way for a better non-invasive evaluation of the risk of relapse when contemplating antitumour necrosis factor α withdrawal in CD patients.